A Comparative Study to Evaluate the Functional Effect of Unilateral Uvuloplasty after Primary Palatoplasty - Rossell-Perry, Percy (Plast Reconstr Surg Glob Open, 2015)
BACKGROUND: The conventional method for uvular repair suturing the 2 hemi-uvulas of the palatal cleft together in the midline does not allow us to obtain a proper anatomical repair. In our hands, the midline straight closure frequently causes retraction of the uvular tissues with the consequent abnormal appearance of the uvula. We described before a method for uvular repair in patients with cleft palate. The technique consists in preserving one of the hemi-uvulas, which is moved to the midline to form the definitive uvula. The purpose of this study was to evaluate the functional effects of the unilateral uvuloplasty for uvular repair in a group of patients with bilateral cleft palate. METHODS: This is a retrospective, single-blinded cohort study between 2 groups of 90 patients with bilateral cleft palate who were operated on using the conventional and unilateral uvuloplasty methods of uvular repair from 2000 to 2009. Data collection was accomplished by physical examination to evaluate the presence of postoperative fistulas and hypernasal speech determined at 6 months to 5 years after surgery. In addition, postoperative dimensions of the velopharynx were measured by a single-blind examiner using a computed tomography scan. RESULTS: Our comparative study found statistically significant differences between the 2 groups in favor of the unilateral uvuloplasty group. CONCLUSIONS: We observed that the use of unilateral uvuloplasty for uvular reconstruction reduces the velopharyngeal space and the frequency of hypernasality in patients with bilateral cleft palate.